Effects of MnO2 on density and microwave dielectric properties of ZnO–Nb2O5–SnO2–TiO2 ceramics with BaCu(B2O5) sintering aid. Issue 1 (January 2016) - Zhang, Yangyang; Dong, Xuefeng; Chen, He; Zhang, Jinping; Gao, Jingxia; Li, Hui
Abstract: The following is an investigation of MnO2 -doped ZNST samples using BaCu(B2 O5 ) as the main sintering aid. The sintering behavior, phase composition, and dielectric properties are observed after being fabricated by the conventional solid-state reaction process. The results show that by adding small amount of MnO2, one can effectively inhibit the formation of the minor crystalline phase Zn0.17 Nb0.33 Ti0.5 O2 while using ZnNb2 TiO8 as the main crystalline phase. This promotes the grain growth, thereby effectively improving the sintering behavior, while optimizing the microwave dielectric performance of the ZNST ceramics. By adding 1 mol% of MnO2, the ZNST ceramics with BaCu(B2 O5 ) sintering aid can be compactly sintered at 850 °C with the microwave dielectric properties of Q×f =16960 GHz, ε r =41.28 and τ f =−16 ppm/°C. This implies that the compound is a good candidate for LTCC applications.